The Business Spirit of Sidogiri Islamic Boarding School Financial Institutions in the Perspective of Entrepreneurship Education - Supriyanto Supriyanto; Wyanet Putri Alisha; Yulhendri Yulhendri; Agung Sudjatmoko (Universitas Indraprasta PGRI, 2022)
The success of the Sidogiri Islamic Boarding School in building a financial business network has been recognized nationally. Sidogiri is a boarding school with the largest business unit in Indonesia. This study aims to interpret the business spirit of Islamic boarding schools. This study uses a case study research design at the Sidogiri Islamic boarding school, Pasuruan. The unit of analysis for this research is the kyai as caregivers, teachers or ustadz, business unit administrators, students, alumni, and the community. Methods of data collection using observation, interviews, analysis of financial statements, and analysis of documentation. Qualitative research design with a case study model. Data analysis and data validity testing used source triangulation, method triangulation, and time triangulation techniques. The findings of this study indicate that (1) the spirit of financial institutions is the religious spirit to leave the business that contains usury, (2) the business education carried out by the Sidogiri Islamic boarding school uses a programmed curriculum in madrasah dinniyah (3) an integrated education curriculum between theory, practice, internship, assignment curriculum to manage financial business units (4) business education is given to students at the senior level madrasah dinniyah with fan mu'amalah (5) students who graduate are given the task of managing financial business units (6) the boarding school together with alumni create business unit branches, and (7 ) business unit management is left to alumni.